Incorporating phosphorus cycling into global modeling efforts: a worthwhile, tractable endeavor. Issue 2 (25th June 2015) - Reed, Sasha C.; Yang, Xiaojuan; Thornton, Peter E.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> 324 I. I. 324 II. II. 325 III. III. 326 IV. IV. 327 328 References 328 </table-wrap> Summary Myriad field, laboratory, and modeling studies show that nutrient availability plays a fundamental role in regulating CO2 exchange between the Earth's biosphere and atmosphere, and in determining how carbon pools and fluxes respond to climatic change. Accordingly, global models that incorporate coupled climate–carbon cycle feedbacks made a significant advance with the introduction of a prognostic nitrogen cycle. Here we propose that incorporating phosphorus cycling represents an important next step in coupled climate–carbon cycling model development, particularly for lowland tropical forests where phosphorus availability is often presumed to limit primary production. We highlight challenges to including phosphorus in modeling efforts and provide suggestions for how to move forward.